A Design of an Induction Method Device with Respect to the Signal and Noise Sensitivity - Blazek, Dalibor; Kudelcik, Jozef; Blazek, Jozef (Communications - Scientific letters of the University of Zilina, 2003)
An objective of this article is the relationship between the signal sensitivity, the noise sensitivity and the distribution of turns of winding on any chosen axis-symmetric core. The analytical study originates from Faraday induction law and Nyquist theorem. Different windings were compared with respect to their physical properties.